Estimulación cerebral y teoría psicologíca - Ardila, Ruben (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Studies of cerebral stimulation following the technique of Olds are examined in relation to psychological theories, above all those of learning. Cerebral stimulation is analyzed as reward, as punishment, the interaction between cerebral stimulation and other impulses (drives), and the similarity between cerebral stimulation and other impulses. It is shown that the theories of learning based on reduction of drives are affected more than the others. On the other hand, Tolman’s theory and the Gestalt theories only require minor revisions, and the system of Skinner is not affected by the work done on cerebral stimulation.